مرتكزات النقد الحداثي عند الرابطة القلمية - لعور, كمال (Université de M'sila, 2020)
الملخص : بلغت الرابطة القلمية مبلغا واسعا من النضج الفني، والحس النقدي، ما جعلها تتبوأ ريادة المبادرة بالثورة على القديم، وعلى الرغم من تواجد فئات وأطياف كثيرة تقتسم معها ساحة الأدب العربي، وتبادلها التيار الرومنسي إلا أن الرابطة القلمية تميزت بتناسق منقطع النظير بين أفرادها، بالارتكاز على فلسفة محددة، وبالتفرد في أسلوب التعبير ما جعلها ثبتت على ثورتها الى آخر أنفاسها، وتبادر بممارسة الحداثة الأدبية بوعي تارة وبانبهار تارة أخرى، ولم يقلل حسها الانطباعي في النقد من أن يكون لدى أدبائها رؤيا متعمقة ذات أبعاد صوفية استشراقية خاصة عند جبران خليل جبران وميخائيل نعيمة. The Penal Association* alrrabitat alqalamia * reached a large amount of artistic maturity and critical sense, which made it the pioneer of the initiative to revolutionize the old, Despite the existence of categories with which the Arab literature arena is shared, and the exchange of the romantic current, the Penal Association was characterized by amazing coordination among its members, Based on a specific philosophy, and uniqueness in the style of expression, which made it proved its revolution to the last breath, and initiates the practice of literary modernity consciously at times and fascinated at other times. Her impressionistic sense of criticism did not diminish her writers' insight into an Orientalist mystical dimension, especially at Gibran Khalil Gibran and Michael Naima.
Keywords: الكلمات الدالة: الرابطة القلمية، نقد، حداثة، الرومنسية: Penal Association, Criticism, Modernity, Romance